Effects of educational technology in relation to the acquisition listening comprehension skill among preschool and kindergarten at Aguacatal Elementary School - Ríos Guerra, Vicky Itzel (UDELAS, 2014)
The integration of technology in education is no longer a new idea because technology has become an essencial part of society. However, it is necessary to integrate its use in education in a variety of ways to help students to acquire english language in aan easy way.